The Relationship Between Medication-Related Burden and Therapy Compliance of Hypertension Patients - Supadmi, Woro; Afifa, Shafira Diestra; Izzah, Fiya Nailil; Gustinanda, Rizky (Sciences of Pharmacy, 2026)
Hypertension prevalence in the Special Region of Yogyakarta (31.8%) is higher than the national average (30.8%), and long-term medication use may create a burden that negatively affects adherence. This study aimed to evaluate the relationship between medication-related burden and adherence among hypertensive outpatients at Panembahan Senopati Bantul Regional Hospital and Yogyakarta City Regional Hospital. Using a cross-sectional design, 161 patients were recruited between January and February 2025. Medication-related burden was assessed with the Living with Medicines Questionnaire version 3 (LMQ-3), while adherence was measured using the Medication Adherence Rating Scale-5 (MARS-5). Most patients experienced a low burden (76.4%), followed by no burden (15.5%) and moderate burden (8.1%). Regarding adherence, 83.2% showed moderate adherence and 16.8% high adherence. Spearman’s correlation analysis revealed a significant negative relationship between medication-related burden and adherence (p=0.000; Rho = -0.461). These findings suggest that a higher treatment burden reduces adherence to antihypertensive therapy, highlighting the need for strategies to minimize patient burden and improve treatment outcomes.